RNA Polymerase III, Ageing and Longevity - Kulaberoglu, Yavuz; Malik, Yasir; Borland, Gillian; Selman, Colin; Alic, Nazif; Tullet, Jennifer M. A. (Frontiers in Genetics, 2021)
Transcription in eukaryotic cells is performed by three RNA polymerases. RNA polymerase I synthesises most rRNAs, whilst RNA polymerase II transcribes all mRNAs and many non-coding RNAs. The largest of the three polymerases is RNA polymerase III (Pol III) which transcribes a variety of short, non-coding RNAs including tRNAs and the 5S rRNA, in addition to other small RNAs such as snRNAs, snoRNAs, SINEs, 7SL RNA, Y RNA, and U6 spilceosomal RNA. Pol III-mediated transcription is highly dynamic and regulated in response to changes in cell growth, cell proliferation and stress. Pol III-generated transcripts are involved in a wide variety of cellular processes, including translation, genome and transcriptome regulation and RNA processing, with Pol III dys-regulation implicated in diseases including leukodystrophy, Alzheimer’s, Fragile X-syndrome and various cancers. More recently, Pol III was identified as a new, evolutionarily conserved determinant of organismal lifespan acting downstream of mTORC1. Pol III inhibition extends lifespan in yeast, worms and flies, and in worms and flies acts from the intestine and intestinal stem cells respectively to achieve this. Intriguingly, Pol III activation achieved through impairment of its master repressor, Maf1, has also been shown to promote longevity in model organisms, including mice. In this review we introduce the Pol III transcription apparatus and review the current understanding of RNA Pol III’s role in ageing and lifespan in different model organisms. We then discuss the potential of Pol III as a therapeutic target to improve age-related health in humans.